The The Effectiveness of Using Pyramid Board Game to Teach Writing at MTs Salafiyah Syafi’iyah - Azizah, Saskia Putri; Agustina, Ria Kamilah (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study aimed to investigate the effectiveness of using the Pyramid Board Game as a medium to improve students’ writing skills. A quasi-experimental method was used involving 60 students of MTs Salafiyah Syafi’iyah Seblak in Kwaron Tebuireng Cukir Jombang in the 2023/2024 academic year. The sample was divided into two groups: the experimental class taught using the Pyramid Board Game and the control class taught using picture series. Writing tests were given in pre-test and post-test stages. The result showed a significant improvement in the experimental class with a mean post-test score of 79 compared to 59.5 in the pre-test, while the control class improved from 60 to 71.3. The independent sample t-test revealed a significance value of 0.005 (p < 0.05), indicating a significant difference between both groups. The use of Pyramid Board Game is successfully engaged students and improved their writing abilities in grammar, vocabulary, and sentence structure.